2016
DOI: 10.1038/srep31933
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Homologous Mutation in the Cation Diffusion Facilitator Protein MamM Causes Single-Domain Structural Loss and Signifies Its Importance

Abstract: Cation diffusion facilitators (CDF) are highly conserved, metal ion efflux transporters that maintain divalent transition metal cation homeostasis. Most CDF proteins contain two domains, the cation transporting transmembrane domain and the regulatory cytoplasmic C-terminal domain (CTD). MamM is a magnetosome-associated CDF protein essential for the biomineralization of magnetic iron-oxide particles in magnetotactic bacteria. To investigate the structure-function relationship of CDF cytoplasmic domains, we char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 73 publications
(120 reference statements)
0
27
0
Order By: Relevance
“…Similar to most characterized CDF transporters, MamB and MamM have been shown to self‐interact and form homodimers (Uebe et al ., ; Zeytuni et al ., ,b; Barber‐Zucker et al ., ). However, MamB and MamM have also been suggested to form heterodimers since both proteins were shown to physically interact.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to most characterized CDF transporters, MamB and MamM have been shown to self‐interact and form homodimers (Uebe et al ., ; Zeytuni et al ., ,b; Barber‐Zucker et al ., ). However, MamB and MamM have also been suggested to form heterodimers since both proteins were shown to physically interact.…”
Section: Introductionmentioning
confidence: 97%
“…CDF family proteins are found in organisms of all domains of life and were shown to exclusively export divalent metal cations from the cytoplasm into the extracellular space or intracellular compartments. As such, CDF proteins contribute to metal ion resistance, signaling or metalation of metalloproteins (Nies, ; Jirakulaporn and Muslin, ; Suzuki et al ., ), with malfunction of human CDF homologues (zinc transporters ZnT1 to ZnT10) having been linked to several diseases, such as hepatomegaly, dystonia, diabetes or Alzheimer's disease (Ohana et al ., ; Barber‐Zucker et al ., ; Perez et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…MamM transports iron from the bacterium cytoplasm into such magnetosomes, which enables synthesis of iron‐based magnetic particles inside the vesicles. In the absence of MamM or in case of mutations that cause its dysfunction, these particles are either not formed or formed defectively . Since such differences in magnetic particle formation in MTB are easy to study, MamM serves as an effective model to study CDF proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Protein purification. All MamM CTD constructs were purified as previously described for MamM CTD M250L and other mutants [20][21][22] . For all experiments, protein concentration was determined by measuring protein absorption at 280 nm.…”
Section: Site-directed Mutagenesis and Protein Expression Mamm Ctd Gmentioning
confidence: 99%
“…Furthermore, mutations in its metal binding sites in both the TMD and CTD cause defective formation of the magnetic particles in vivo 10,14 . MamM CTD was well characterized in vitro: its crystal structure revealed that it has the characteristic fold of CDF proteins; the CTD structure was shown to be crucial for the overall protein function; DDMC binding to the CTD causes a conformational change from a dynamic-apo form to a rigid, more closed V-shaped structure; and it binds different DDMCs distinctively 14,16,20,21 .…”
Section: Introductionmentioning
confidence: 99%